2014
DOI: 10.1111/epi.12632
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent generalized seizures, visual loss, and palinopsia as phenotypic features of neuronal ceroid lipofuscinosis due to progranulin gene mutation

Abstract: Summary We detail the phenotype of a novel form of neuronal ceroid lipofuscinosis due to a homozygous progranulin gene mutation (c.813_816del; CLN11 MIM #614706). The symptoms appeared in two young adult siblings, and included progressive retinopathy, recurrent generalized seizures, moderate ataxia, and subtle cognitive dysfunction. Long‐lasting episodes of palinopsia were a recurring symptom and associated with polyphasic visual‐evoked potential waveform that suggested hyperexcitability of the occipital corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 13 publications
4
38
1
Order By: Relevance
“…Electron microscopy analysis showed some consistency with previous findings (e.g. CLN11), whereas the CLN3 patient in this study showed curvilinear bodies in contrast to a study highlighting fingerprint patterns as the major inclusion type …”
Section: Discussionsupporting
confidence: 90%
“…Electron microscopy analysis showed some consistency with previous findings (e.g. CLN11), whereas the CLN3 patient in this study showed curvilinear bodies in contrast to a study highlighting fingerprint patterns as the major inclusion type …”
Section: Discussionsupporting
confidence: 90%
“…Vision loss and retinal atrophy are early phenotypes in most patients with NCL. Our recent observations of moderate retinal thinning in heterozygous GRN mutation carriers, compared to nearly complete vision loss and severe retinal atrophy in homozygous GRN mutation carriers (18), suggest a relationship between GRN gene dosage and the severity of retinal involvement. We also found that lipofuscinosis and membrane-bound storage material deposition—pathologic hallmarks of NCL—occurred in heterozygous GRN mutation carriers, consistent with what has been seen in homozygous GRN mutation carriers.…”
Section: Discussionmentioning
confidence: 77%
“…Approximately 5% of the CLN mutations have been associated with adult-onset neurological phenotypes (from 17 to 43 yrs) divided into three different subtypes: Kufs diseases, characterized by progressive myoclonus epilepsy and cognitive decline (Type A), or behavioral anomalies, dementia, motor dysfunction, ataxia and extrapyramidal and suprabulbar signs (Type B) [4,18]; adult NCLs which include autosomal dominant Parry disease due to DNJC5 mutations [13] and the recessive NCL type 11 associated with mutations in the progranulin gene [7] (Table 1).…”
Section: Discussionmentioning
confidence: 99%